MBG scaffolds containing chitosan microspheres for binary delivery of IL-8 and BMP-2 for bone regeneration. Issue 27 (27th June 2018) - Cai, Lisha; Lin, Dan; Chai, Yanjun; Yuan, Yuan; Liu, Changsheng
Abstract : Illustration of the binary protein release in a bone regenerative process. Abstract : Biomimetic delivery of chemokines and growth factors based on stem cell recruitment and endochondral ossification, as the key steps in natural regenerative process, has been an area of intense research in recent years. An inflammatory chemokine, interleukin-8 (IL-8), was recently reported with high recruitment efficiency of bone marrow stem cells, chondrogenic inductivity and immune regulatory functions. In this study, the effect of IL-8 action duration on bone morphogenetic protein-2 (BMP-2)-induced bone regeneration was studied to achieve an optimal synergism of these two proteins. Herein, a mesoporous bioactive glass (MBG)-based scaffold with BMP-2 entrapment and IL-8-loaded chitosan microspheres (CMs) was developed. The MBG scaffold with size-matched mesopores was adopted for the long-term sustained delivery of BMP-2; and CMs with different sizes, prepared using a modified ionotropic gelation method, were customized to match the optimal action time of IL-8. The results indicated that CMs of 100 μm diameter and medium crosslinking density exhibited an 85% release of IL-8 in 7 days and the MBG substrate exhibited a long-term sustained release of BMP-2. Furthermore, the binary delivery system exhibited excellent biocompatibility and synergistically enhanced osteoinductivity. In an in situ bone regeneration model of a rabbit radius large segmental defect, the system efficiently accelerated the whole regenerative process, with the highest bone formation amount from an early stage and the highest degree of regenerative completion. Since delivery systems for multiple cytokines have been in great demand due to the requirement of complicated biological processes, we believe that this new binary delivery system could be customized to design other dual delivery systems for improving bone-repairing biomaterials with higher regenerative efficiency.